Does Innovation Help the Good or the Poor Performing Firms? - Jože P. Damijan; Črt Kostevc; Matija Rojec (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2009)
Using firm-level innovation data for a large sample of Slovenian firms in the period 1996-2002, the paper finds surprising results that innovation is not benefitting all firms. We find that only manufacturing firms with below average productivity growth (the lowest four deciles) are likely to experience significant benefits from successful innovation, while faster growing firms do not extract any additional benefits from innovation. This evidence demonstrates how innovation can affect the observed convergence of firms in tfirms of productivity in the manufacturing sector.
Keywords: D24; 330; research and development; innovation; knowledge spillovers; productivity growth; Industrielle Forschung; Innovationsdiffusion; Spillover-Effekt; Unternehmenserfolg; Produktivität; Slowenien